2022
DOI: 10.1111/1348-0421.12965
|View full text |Cite
|
Sign up to set email alerts
|

Secondary streptococcal infection following influenza

Abstract: Secondary bacterial infection following influenza type A virus (IAV) infection is a major cause of morbidity and mortality during influenza epidemics. Streptococcus pneumoniae has been identified as a predominant pathogen in secondary pneumonia cases that develop following influenza. Although IAV has been shown to enhance susceptibility to the secondary bacterial infection, the underlying mechanism of the viral–bacterial synergy leading to disease progression is complex and remains elusive. In this review, coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 122 publications
0
14
0
Order By: Relevance
“…IAV infects the upper respiratory tract and oral mitis group streptococci are inhabitants of the oral cavity [2,6,[33][34][35]. The interaction between IAV and S. pneumoniae, a pathogenic member of the mitis group, have been intensively investigated [2,20,21,[36][37][38][39]; however, the interaction between IAV and oral streptococci has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IAV infects the upper respiratory tract and oral mitis group streptococci are inhabitants of the oral cavity [2,6,[33][34][35]. The interaction between IAV and S. pneumoniae, a pathogenic member of the mitis group, have been intensively investigated [2,20,21,[36][37][38][39]; however, the interaction between IAV and oral streptococci has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Poor oral hygiene is reported to be correlated with occurrence of respiratory diseases such as bacterial pneumonia [16], and professional oral healthcare has been shown to reduce the risk of IAV infection [17]. The interaction between IAV and S. pneumoniae has been intensively investigated [15,[18][19][20][21], however, interaction between IAV and oral streptococci is not well understood. Several studies have shown that neuraminidase (NA)-producing streptococci such as S. pneumoniae and oral mitis group streptococci potentially elevate the risk of influenza because NA plays an essential role in IAV infection [13,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial co-infections with viruses represent a considerable challenge to public health, and for S. pneumoniae, influenza virus is the major pathogen leading to secondary pneumococcal infections (13). Antibiotic-resistance further compounds the difficulty of treating co-infected patients (41), so the search for alternative therapies is of significant importance. Influenza virus is able to suppress alveolar macrophage cell function within 7 days of infection (22,42).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that acidification of the airway fluids during infection mitigates the effectiveness of the AMPs, facilitating common co- or secondary-infection with Streptococcus pneumoniae in the respiratory epithelium caused by influenza [ 137 ]. Proximal IAV infection would appear to be stimulated by the neuraminidase-expressing streptococci, which include certain oral mitis group streptococci.…”
Section: Spectrum Of Amp Activity Across Microbial Kingdomsmentioning
confidence: 99%